A detailed techno-economic analysis of heat integration in high temperature electrolysis for efficient hydrogen production. (5th January 2015) - Buttler, Alexander; Koltun, Roman; Wolf, Romano; Spliethoff, Hartmut
Abstract: The effect of high temperature heat utilization in solid oxide electrolysis on efficiency and hydrogen specific cell area is investigated based on a detailed 1-D electrochemical model validated with literature data. A first feasibility analysis indicates that the mean heat transfer required to maintain isothermal conditions as a function of heat integration shows a maximum with 1426 W/m 2 at a heat utilization of 0.34 kWh/Nm 3 H2, which seems to be technically achievable. Based on the assumption of future specific cell area costs of 1500 €/m 2 high temperature heat integration of 0.24 kWh/Nm 3 is economically reasonable resulting in a reduction of the specific electric energy consumption by 7.8% (2.82 kWh/Nm 3 ) compared to thermo-neutral operation. An extensive sensitivity analysis indicates increased electricity prices and higher lifetime of the solid oxide electrolysis cell (SOEC) stack as major parameters favoring direct heat utilization, while decreasing utilization for power-to-gas storage applications is counteracting. Highlights: A detailed numerical model of solid oxide electrolysis is derived and validated. Integration of high temperature heat for efficiency improvement is analyzed. A first feasibility analysis of high temperature heat integration is conducted. Heat integration is favored by high electricity prices, SOEC lifetime or capacity utilization and low SOEC investment costs.